PEMBUATAN KARYA SENI MENGGAMBAR DEKORATIF PADA TALENAN KAYU DI KELAS IIIB SDN 04 KOTA BENGKULU - Rina Wati, Nova (Universitas Bengkulu, 2024)
This study aims to describe the process and decorative drawings on a wooden cutting board in class III B Public Elementary School 04 Bengkulu City. The types and methods are qualitative research and descriptive methods with participatory observation techniques. The subjects in this study were students of class III B Public Elementary School 04 Bengkulu City, totaling 30 people. The research instrument is a human instrument. Data collection techniques using observation, interviews, and documentation. Data analysis is performed by analyzing the data then displaying the data, data condensation and drawing conclusions. Data analysis of the work is discussed by looking at the elements of fine arts and the principles of art. The research results obtained by researchers are that of the 15 students' work there are plant motifs, animal motifs, stylation motifs, and geometric motifs. The process of making decorative artwork on a wooden cutting board by students begins with preparing tools and materials, giving basic paints, making design motifs, and coloring the motifs as a solution. The works of decorative drawing on wooden cutting boards have used fine arts elements and fine arts principles. but the dark light element is not used.